2020
DOI: 10.1038/s41598-020-69542-6
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of T lymphocyte subsets and B lymphocytes in response to immunostimulants in flounder (Paralichthys olivaceus): implications for CD4+ T lymphocyte differentiation

Abstract: CD4 + T lymphocytes play crucial roles in the adaptive immune system. CD4, as the most effective marker to delineate the T-helper subsets, was identified in many fish species. Two CD4 homologs, CD4-1 and CD4-2, have been reported in flounder (Paralichthys olivaceus). In this study, monoclonal antibodies (mAbs) against CD4-1 and CD4-2 of flounder were produced, CD4 + T lymphocytes were isolated and identified, and the variations in CD4 + and CD8 + t lymphocytes and igM + B lymphocytes after Poly I:C, PMA or β-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…As important immune cells, T/B lymphocytes play an irreplaceable role in cellular and humoral immunity in fish. In our previous study, the monoclonal antibodies against flounder IgM, CD4-1, CD4-2, and polyclonal antibodies against flounder CD8β molecule were produced, respectively, T and B lymphocytes were identified and characterized in flounder ( 29 31 ). In this study, T-bet was found to be expressed in sorted IgM + B lymphocytes, and also in CD4-1 + , CD4-2 + , and CD8 + T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As important immune cells, T/B lymphocytes play an irreplaceable role in cellular and humoral immunity in fish. In our previous study, the monoclonal antibodies against flounder IgM, CD4-1, CD4-2, and polyclonal antibodies against flounder CD8β molecule were produced, respectively, T and B lymphocytes were identified and characterized in flounder ( 29 31 ). In this study, T-bet was found to be expressed in sorted IgM + B lymphocytes, and also in CD4-1 + , CD4-2 + , and CD8 + T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few functional studies have been carried out on fish CD4 + cells due to a lack of tools. Recently, monoclonal antibodies against CD4 molecules were generated for ginbuna crucian carp, rainbow trout, and flounder ( 31 , 53 , 54 ). CD4 + cells have been identified using monoclonal antibodies, and the function of teleost CD4 + cells was demonstrated to be similar to that of mammalian Th cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AB082957.1 andAB643633.1) were translated using Expasy (https://web.expasy.org/translate/). The signal peptide, transmembrane domain and immunoglobulin-like domains were predicted using Signal P 4.1 (http://www.cbs.dtu.dk/ services/SignalP-4.1/), TMHMM 2.0 (http://www.cbs.dtu.dk/services/TMHMM-2.0/) and SMART software (http://smart.embl-heidelberg.de/), respectively [37]. The secondary structures and the physico-chemical characteristics of amino acids, including antigenicity, hydrophobicity, charge density and flexibility were analyzed using DNAStar Protean program.…”
Section: Synthesis Of Cd8α-and Cd8β-peptidesmentioning
confidence: 99%